ENLIGHTENING THE CONCEPT OF UPASAYA AND ITS ROLE IN DIAGNOSIS AND CHIKITSA ASPECT (AYUSHDHARA, 2017)
Diagnosis in Ayurveda is usually based on five techniques called as Pancha lakshananidanas, which are used to identify and diagnose any kind of disease along with the root cause of occurrence of disease. The word Pancha lakshana Nidanas constitutes combination of two words Pancha means five and Nidana means methods of diagnosis.The five types of Nidanas include Nidana (cause), Purvarupa (prodromal symptoms), Rupa (symptoms), Upashaya (exploratory methods) and Samprapti (manifestation of disease).In Ayurveda Pancha nidana deploys a proper diagnostic method where one factor can result in numerous diseases. For e.g., aggravation of Vata dosha in the body can lead to around eighty diseases. Hence, it is important for Ayurvedic practitioners to have proper knowledge of all types of Dosas i.e., Vata, Pitta and Kapha, Srotas, Dhatus, Trigunas and other systems of the body in order to diagnose the exact cause of the disease and to plan best remedial measures.There are many ailments likely to have similar cause and symptoms. Upashaya is an ancient Ayurvedic technique to differentiate and diagnose such disorders and to plan accurate remedial measures Upashaya also includes various diet regulations depending on the individuals suitability and the stage of the disease.Based upon the ancient treatises like Charaka samhitha, Susruta samhitha, Vagbhata samhitha, Madhava nidana In the present study an attempt has been made to understand the applicability of Upasaya in the diagnosis aspect especially for knowing the Doshic involvement as well as in treatment aspect for selecting the appropriate line of treatment for the ailments.